Millenials’ Perception: Lampu Islam Da’wah Content as a Spiritual Counseling on YouTube Social Media - Pratama, Muhammad Farid; Mutrofin; Moh. Khoerul Anwar; Fadil (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2023)
Along with the development of the times and technology, the process of delivering da'wah has changed. Social media is a form of technological development and an alternative media for providing da'wah, one of which is YouTube. Every preacher or content creator tries to convey da'wah by loading packaged content attractively so that it doesn't seem monotonous and can attract the wider community. The Lampu Islam YouTube channel does this by spreading da'wah and Islamic content that is packaged in an attractive and varied way. The public sees that the da'wah content in Lampu Islam will create a particular perception, as well as providing counseling services, especially in spiritual counseling. This study aims to determine the perceptions and spiritual counseling of millennials towards Lampu Islam da'wah content on YouTube social media. The research method used is the descriptive qualitative method. The data was collected through interviews, observation, and documentation. The subject of this research focuses on millennials who live in Tulungagung. The study results show that millennials positively perceive da'wah content on the Lampu Islam channel as well as becoming a spiritual counseling. Millennials perceive that Lampu Islam is a channel that has a variety of da'wah and Islamic content that is interesting, creative, and informative. Informants perceive that the content of Lampu Islam preaching has sufficient duration and is not dull. The nature of the preacher is quite clear and straightforward so that the material provided can be easily understood.